Acetaldehyde at clinically relevant concentrations inhibits inward rectifier potassium current I(K1) in rat ventricular myocytes - Bébarová, M; Matejovič, P; Šimurdová, M; Šimurda, J (Physiological research, 2015)
Considering the effects of alcohol on cardiac electrical behavior as well as the important role of the inward rectifier potassium current I(K1) in arrhythmogenesis, this study was aimed at the effect of acetaldehyde, the primary metabolite of ethanol, on I(K1) in rat ventricular myocytes. Acetaldehyde induced a reversible inhibition of I(K1) with IC(50) = 53.7+/-7.7 microM at -110 mV; a significant inhibition was documented even at clinically-relevant concentrations (at 3 microM by 13.1+/-3.0 %). The inhibition was voltage-independent at physiological voltages above -90 mV. The I(K1) changes under acetaldehyde may contribute to alcohol-induced alterations of cardiac electrophysiology, especially in individuals with a genetic defect of aldehyde dehydrogenase where the acetaldehyde level may be elevated.
Keywords: Potassium Channels, Inwardly Rectifying; Alcoholic Intoxication; Patch-Clamp Techniques; otrava alkoholem; Animals; Male; potkani Wistar; metoda terčíkového zámku; zvířata; draslíkové kanály dovnitř usměrňující; Myocytes, Cardiac; Rats, Wistar; kardiomyocyty; acetaldehyd; mužské pohlaví; Acetaldehyde